Neutrophils Lose the Capacity to Suppress T Cell Proliferation Upon Migration Towards Inflamed Joints in Juvenile Idiopathic Arthritis - Arve-Butler, Sabine; Mossberg, Anki; Schmidt, Tobias; Welinder, Charlotte; Yan, Hong; Berthold, Elisabet; Król, Petra; Kahn, Robin (Frontiers in Immunology, 2022)
Neutrophils are highly abundant in synovial fluid of rheumatic inflamed joints. In oligoarticular juvenile idiopathic arthritis (JIA), synovial fluid neutrophils have impaired effector functions and altered phenotype. We hypothesized that these alterations might impact the immunoregulatory interplay between neutrophils and T cells. In this study we analyzed the suppressive effect of neutrophils, isolated from blood and synovial fluid of oligoarticular JIA patients, on CD4+ T cells activated by CD3/CD28 stimulation. JIA blood neutrophils suppressed T cell proliferation but synovial fluid neutrophils from several patients did not. The loss of T cell suppression was replicated in an in vitro transmigration assay, where healthy control neutrophils migrated into synovial fluid through transwell inserts with endothelial cells and synoviocytes. Non-migrated neutrophils suppressed proliferation of activated CD4+ T cells, but migrated neutrophils had no suppressive effect. Neutrophil suppression of T cells was partly dependent on reactive oxygen species (ROS), demonstrated by impaired suppression in presence of catalase. Migrated neutrophils had reduced ROS production compared to non-migrated neutrophils. A proteomic analysis of transwell-migrated neutrophils identified alterations in proteins related to neutrophil ROS production and degranulation, and biological processes involving protein transport, cell-cell contact and inflammation. In conclusion, neutrophils in synovial fluid of children with JIA have impaired capacity to suppress activated T cells, which may be due to reduced oxidative burst and alterations in proteins related to cell-cell contact and inflammation. The lack of T cell suppression by neutrophils in synovial fluid may contribute to local inflammation and autoimmune reactions in the JIA joint.